2016
DOI: 10.1590/1807-7692bar2016160028
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cluster, Innovation and Export Performance: An Empirical Study

Abstract: Regional clusters and innovations in product and processes are found in the literature as important determinants of firms' export performance. However, this relationship is still controversial and very highly constrained by industry, and by regions. Based on a more integrative perspective, the aim of the present article is to investigate the role of agglomeration economies of a regional cluster on the export performance of firms. Furthermore, we will test the mediating effect of innovation and the extent by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
0
15
0
7
Order By: Relevance
“…Merino et al (2018) emphasize that the opening of innovative processes can lead to the increase of potential and effective consumers Silva et al (2016) investigated the relationships of small business partnerships with external agents, and their results showed that the relationship between external agents and small firms favors innovative performance. In regional clusters, Prim et al (2016) found that firms that access additional resources with greater intensity tend to improve product and process innovation and export performance.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…Merino et al (2018) emphasize that the opening of innovative processes can lead to the increase of potential and effective consumers Silva et al (2016) investigated the relationships of small business partnerships with external agents, and their results showed that the relationship between external agents and small firms favors innovative performance. In regional clusters, Prim et al (2016) found that firms that access additional resources with greater intensity tend to improve product and process innovation and export performance.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…Ainda segundo os autores, uma estratégia orientada para o cluster pode ser identificada por acontecimentos como: reuniões entre negócios, programação de eventos, presença de assessoria específica e ações voltadas para a competitividade do agrupamento. fornecedores, clientes, concorrentes e empresas relacionadas; e os recursos institucionais representam organizações educacionais, profissionais e organizações de governança do cluster, aqui denominadas, organizações de apoio (Prim, Amal & Carvalho, 2016).…”
Section: Clusters E Competitividadeunclassified
“…These specialized skills do promote social networks and relationships that are stable as there is exchange of knowledge through interaction or through practicing over a period of time (Gereffi & Lee, 2016;Newman, Page, Rand, Shimeles, Söderbom, & Tarp, 2016). Evidently, it can be seen that firms within an industry cluster turn to be more innovative and competitive than those outside the cluster (Branco & Lopes, 2018;Lindberg & Säll, 2013;Porter, 2000) because an empirical evidence by Prim et al (2016) proves that a significant source by which firms can generate innovation, competition and sustenance is through agglomeration economies of a cluster. The operational patterns of clusters have the flexibility in adjusting to uncertain business transformations (Purwanto, Kamaruddin, & Mohamad, 2015;He, Rayman-Bacchus, & Wu, 2011) and may explain why cluster entities that are not properly connected fail (Bankova, 2015;McCormick, 1998).…”
Section: Industry Clustermentioning
confidence: 99%